2015
DOI: 10.1038/modpathol.2014.149
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of p16INK4a in oral cavity carcinomas: p16Ink4A dampens tumor invasion—integrated analysis of expression and kinomics pathways

Abstract: A large body of evidence shows that p16 INK4a overexpression predicts improved survival and increased radiosensitivity in HPV-mediated oropharyngeal squamous cell carcinomas.(OPSCC). Here we demonstrate that the presence of transcriptionally active HPV16 in oral cavity squamous cell carcinomas does not correlate with p16 INK4a overexpression, enhanced local tumor immunity, or improved outcome. It is interesting that HPVmediated oropharyngeal squamous cell carcinomas can be categorized as having a 'nonaggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…30 Dong et al 31 observed that homozygous p16 deletion was significantly more frequent in pT3 and pT4 tumours as compared to pT1 and pT2 tumours in their cohort of 30 cases of buccal SCC. Using OSCC derived cancer cell lines, Isayeva et al 5 demonstrated that p16 overexpression radically decreased tumour invasiveness by the reduction of matrix metalloproteinases (MMP-1 and MMP-9). MMPs are associated with bone invasion.…”
Section: Discussionmentioning
confidence: 99%
“…30 Dong et al 31 observed that homozygous p16 deletion was significantly more frequent in pT3 and pT4 tumours as compared to pT1 and pT2 tumours in their cohort of 30 cases of buccal SCC. Using OSCC derived cancer cell lines, Isayeva et al 5 demonstrated that p16 overexpression radically decreased tumour invasiveness by the reduction of matrix metalloproteinases (MMP-1 and MMP-9). MMPs are associated with bone invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 100 ng RNA was prepared in a 30 µl reaction volume and run on the automated nCounter system. Quality control and normalization were performed on the raw data using positive and negative control spots on the included GX Human Cancer Reference Panel chip and five housekeeping reference genes (16,17). …”
Section: Methodsmentioning
confidence: 99%
“…For instance, p16-positive oropharyngeal carcinomas also display a less locally invasive phenotype, which may account for improved outcomes. p16Ink4a overexpression in oral cavity tumour cell lines decreases tumour invasiveness by affecting extracellular matrix remodelling and expression of matrix metalloproteinases potentially accounting for the observation that p16-positive tumours are less locally invasive [56]. Additionally, in a cohort of primarily p16-positive oropharyngeal cancers that were surgically managed, nodal extracapsular extension, unless the node was completely obliterated, was not associated with poorer outcomes, as has been well established in HPV-negative HNSCC, suggesting a less locally aggressive phenotype in HPV-positive disease [5759].…”
Section: Phenotypic Differences Unrelated To Therapeutic Sensitivitymentioning
confidence: 99%